2020
DOI: 10.1126/sciadv.abc0496
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of blood clots: Mechanics and pathophysiology

Abstract: Fibrin is the three-dimensional mechanical scaffold of protective blood clots that stop bleeding and pathological thrombi that obstruct blood vessels. Fibrin must be mechanically tough to withstand rupture, after which life-threatening pieces (thrombotic emboli) are carried downstream by blood flow. Despite multiple studies on fibrin viscoelasticity, mechanisms of fibrin rupture remain unknown. Here, we examined mechanically and structurally the strain-driven rupture of human blood plasma–derived fibrin clots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 39 publications
2
66
1
Order By: Relevance
“…11 To further compare the blood clots with other materials, we collected the dissipative and nonlinear elastic length scales for various materials. Figure 5B illustrates the values for human WB and PPP clots from this work, and those reported in literature for fibrin gel 8 , blood vessel 28,29 , skin, 30 natural rubber, 31 alginate gels, 30 double-network (DN) gels, 11,32 polyacrylamide (PAAm) gels, 30 PAAm-alginate gels, 30 agar gels, 33 and tetra-arm polyethylene glycol (Tetra-PEG) gels 34 . Compared with the fibrin clot 8 , the WB clots have a smaller flaw sensitivity length scale (~0.2 mm) and larger nonlinear length scale (~7 mm), reflective of the fact that the WB clots contain large fraction of blood cells.…”
Section: Length Scales Of Blood Clot Fracturementioning
confidence: 82%
See 2 more Smart Citations
“…11 To further compare the blood clots with other materials, we collected the dissipative and nonlinear elastic length scales for various materials. Figure 5B illustrates the values for human WB and PPP clots from this work, and those reported in literature for fibrin gel 8 , blood vessel 28,29 , skin, 30 natural rubber, 31 alginate gels, 30 double-network (DN) gels, 11,32 polyacrylamide (PAAm) gels, 30 PAAm-alginate gels, 30 agar gels, 33 and tetra-arm polyethylene glycol (Tetra-PEG) gels 34 . Compared with the fibrin clot 8 , the WB clots have a smaller flaw sensitivity length scale (~0.2 mm) and larger nonlinear length scale (~7 mm), reflective of the fact that the WB clots contain large fraction of blood cells.…”
Section: Length Scales Of Blood Clot Fracturementioning
confidence: 82%
“…Because blood clots are soft (shear modulus < 1 kPa) and deformable, this excludes using conventional fracture testing methods, such as three-point bending methods that are only applicable to rigid materials. 9 Furthermore, because blood clots have low tensile strength <1 kPa, 8 they are vulnerable to damage and even rupture during handling, transport and mounting, especially with a pre-crack introduced. It is problematic for many testing methods such as pure shear tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical defects and cracks within the blood clots make the thrombus more susceptible to rupturing. Thus, clot composition and geometry play a pivotal role in the pathogenesis of ENT 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite this awareness, information on fibrin viscoelasticity, mechanical strength, and mechanisms of fibrin rupture remain unknown. A recent bilateral study, between the US and Russian scientists demonstrated, that rupture resistance of clots and thrombi, determines the incidence of thrombotic embolism, in pathological conditions associated with changes in cellular and molecular blood composition, such as hypo or hyperfibrinogenemia, variations in platelet or leucocyte count as well as hematocrit [12].…”
mentioning
confidence: 99%